Multi-band luminescent ZnO/ZnSe core/shell nanorods and their temperature-dependent photoluminescence. Issue 100 (17th October 2016) - Yang, Xu; Yang, Qin; Hu, Zhigao; Zhang, Wu; Li, Hui; Li, Lequn; Qiu, Yining; Xu, Ning; Wu, Jiada; Sun, Jian
Abstract : Aligned heterostructured ZnO/ZnSe core/shell nanorods are capable of emitting multi-band luminescence which shows a strong temperature dependence. Abstract : We report on the multi-band emission from one-dimensional heterostructured ZnO/ZnSe core/shell nanorods (NRs) and its temperature dependence. Aligned ZnO/ZnSe core/shell NRs constructed of wurtzite ZnO cores and zinc blende ZnSe shells were fabricated by hydrothermal growth of ZnO NRs and pulsed laser deposition of ZnSe coatings on the grown ZnO NRs. The presence of the ZnSe shells outside the ZnO NR cores strongly suppresses the radiative recombination of photogenerated electrons and holes in ZnO and consequently quenches the photoluminescence from ZnO NRs. The suppression of the radiative recombination associated with different transitions in ZnO behaves very differently at different temperatures. At room temperature, the ZnSe-coated ZnO NRs are capable of emitting a multi-band luminescence including a UV emission centered at ∼378 nm, a blue emission centered at ∼462 nm and a broad band emission ranging from 500 to 720 nm. The spectral feature of the multi-band luminescence is strongly dependent on temperature, suggesting the possibility of tuning the emitted light by simply varying the temperature and an approach to broad-band or even full-color emission from the multi-band fluorescent ZnO/ZnSe core/shell NRs.